2005
DOI: 10.1111/j.1467-9310.2005.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Talented suppliers? Strategic change and innovation in the UK aerospace industry

Abstract: The 1990s marked the start of extensive re‐structuring in the aerospace industry throughout the world. While the ensuing consolidation among prime contractors has been widely researched, the changes affecting the aerospace supplier base have received less attention. This exploratory study focuses on the supplier base and points to extensive re‐structuring. Unlike many earlier studies, the lean supply model was found to be a rather powerful influence, with suppliers moving away from subcontractor status and tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 20 publications
0
52
0
1
Order By: Relevance
“…Recent work on the 'innovation value chain' has shown that knowledge inputs from direct collaborative relationships with a variety of sources can have a positive impact on innovation (Roper et al 2008, Ganotakis and). We therefore allow for the effect of knowledge linkages to customers or suppliers (Joshi and Sharma, 2004;Love and Mansury, 2007;Smith and Tranfield, 2005), horizontal linkages to competitors or other sectoral firms (Hemphill, 2003) and linkages to universities or other public research centres (Roper et al, 2004;Del Barrio-Castro and Garcia-Quevedo, 2005). In each case the metric used is a dummy variable indicating whether the firm had a collaborative agreement with the relevant partner.…”
Section: Model and Variablesmentioning
confidence: 99%
“…Recent work on the 'innovation value chain' has shown that knowledge inputs from direct collaborative relationships with a variety of sources can have a positive impact on innovation (Roper et al 2008, Ganotakis and). We therefore allow for the effect of knowledge linkages to customers or suppliers (Joshi and Sharma, 2004;Love and Mansury, 2007;Smith and Tranfield, 2005), horizontal linkages to competitors or other sectoral firms (Hemphill, 2003) and linkages to universities or other public research centres (Roper et al, 2004;Del Barrio-Castro and Garcia-Quevedo, 2005). In each case the metric used is a dummy variable indicating whether the firm had a collaborative agreement with the relevant partner.…”
Section: Model and Variablesmentioning
confidence: 99%
“…More specifically, we identify five different types of knowledge sourcing activity which might shape firms' innovation: in-house R&D (Shelanski and Klein 1995); forward linkages to customers (Joshi and Sharma 2004;Love and Mansury 2007); backward links to either suppliers or external consultants (Horn 2005;Smith and Tranfield 2005); horizontal linkages to either competitors or through joint ventures (Hemphill 2003;Link, Paton, and Siegel 2005); and, linkages to universities or other public research centres (Del Barrio-Castro and Garcia-Quevedo 2005). We then allow for potential complementarities or substitute relationships between knowledge derived from different sources (Veugelers and Cassiman 1999;Love and Roper 2004).…”
mentioning
confidence: 99%
“…Faced with the problem of trying to span an ever greater range of technologies in developing modern airliners, airframe manufacturers have relinquished responsibility for the development and manufacture of many of the larger modules and sub-systems such as wings, fuselage barrels, landing gear and avionics (Cooke and Ehret, 2009;Ehret and Cooke, 2010). Instead these modules are increasingly designed, developed and manufactured by specialist suppliers who not only undertake manufacturing but extensive research and development (McGuire et al, 2010;Smith and Tranfield, 2005). These specialist suppliers are much more than mere subcontractors called upon to manufacture components on a 'build-to-print' basis (Smith and Tranfield, 2005).…”
Section: Actorsmentioning
confidence: 99%
“…Instead these modules are increasingly designed, developed and manufactured by specialist suppliers who not only undertake manufacturing but extensive research and development (McGuire et al, 2010;Smith and Tranfield, 2005). These specialist suppliers are much more than mere subcontractors called upon to manufacture components on a 'build-to-print' basis (Smith and Tranfield, 2005). They have a significant level of capability especially with regard to research and development.…”
Section: Actorsmentioning
confidence: 99%